EXPERIENCES OF RESTAURANT BUSINESS IN THE COVID-19: EVIDENCE FROM RAJSHAHI CITY, BANGLADESH - Kuddus, Md. Abdul; Rahman, Naima; Sarkar, Anusuya (Bangladesh Journal of Multidisciplinary Scientific Research, 2021)
The restaurant business in Bangladesh has no institutional recognition. It has no mentionable business guidelines and juridical structures to combat any epidemic like coronavirus diseas-19 (COVID-19). Because of not having a legitimate basis this sector is suffering a serious financial crisis in the global pandemic. Revenues generating ability has drastically decreased when the government ordered for shutting down the non-essential organization to fight against the spreading the coronavirus. At the same time government also imposes stay order on various special programs like weeding, birthday, new-year celebration, and Iftar party which is directly related to restaurant business. This article, therefore, focuses on the impact of COVID-19 in the restaurant business in Bangladesh. Data were collected through purposive sampling method through a questionnaire. For analyzing the data the statistical package for the social science (SPSS) v. 24.0 was applied. Datasets were analyzed with a statistical tool named Pearson’s correlation coefficient (PCC). Descriptive statistics such as the frequency distribution and graph were also used for presenting and interpreting data. One sample t-test and dependent sample t-test were used to test the hypothesis. The COVID-19 decreases the revenues drastically (r = 0.904, p = 0.000). This is leading to the severe sufferings of workers and owners of the restaurants both fast food and general hotels, the restaurants and convention centers. This deteriorating condition will further be on the increase of the government incentives providing policy needs of the most vulnerable groups in the country in the coming months. Otherwise this small and medium sector will go out of the economy for sine die. From this research, it was apparent that if the educational institutions are not re-opened, the infections rate curve wipe out and the vaccine is not made the restaurant business will not see any good news for booming their business. Coordinated administrative systems, reinforce of the health sector, economy, industry, agriculture and food security should be focused on under the new normal standard of life.